INDONESIAN MUSLIM WOMEN TOURIST: MOTIVATION AND NEEDS IN TOURIST DESTINATION - Dina Hariani; Puput Dewi Anggraeni (Jurnal Ilmiah Hospitality, 2022)
Muslim women who travel continue to increase every year, whether solo traveling, with friends, or with family. As a Muslim, especially a woman, there are obligations that must be carried out when traveling. Muslim women must also be more careful when traveling because Islamophobia and discrimination against them still exist. A Muslim woman is obliged to perform worship 5 times a day, eat halal food, and maintain her appearance. Halal tourism is undoubtedly necessary to fulfill Muslim women's needs. This study aims to examine the typology, motivation, and needs of Indonesian Muslim women who travel. Indonesia is a vast country that is influenced by indigenous and foreign cultures, allowing for differences in typology, motivation, and needs between Indonesian Muslim women and Muslim women from other countries. A study published by Crescent Rating in 2019 has identified the following “key faith-based needs for Muslims travelers” including Halal food, prayer facilities, water-usage friendly washrooms, Ramadhan services, avoidance of non-Halal activities, recreational facilities, and services with privacy (gender segregation). This study also tries to answer whether the needs of Indonesian Muslim women tourists are in accordance with the study of Halal tourism by Cresent Rating. The method used in this study is a descriptive method with a quantitative approach. The data collection method used was convenience sampling of Indonesian Muslim Women tourists with various backgrounds with age at least 18 years old. This research is expected to help stakeholders to fulfill the needs of Indonesian female Muslim tourists during the post-Covid-19 pandemic.